ANALISA PENGARUH DERAJAT KEMIRINGAN TERHADAP KINERJA ELECTRIC TROLLEY TABUNG GAS OKSIGEN DI RSUD ABEPURA - Costantinus Oei; Maran Gultom; Obet Takke Ranteallo (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2023)
The demand for quick and easy distribution of oxygen cylinders at Abepura Regional General Hospital (RSUD Abepura) is increasing. Every operator, nurse, and patient desires quality in the hospital service process. This research explains how to build an automated and time-saving transportation system for oxygen cylinders to facilitate medical services efficiently, environmentally friendly, and safely. This is crucial due to the road conditions at RSUD Abepura, which have particular inclinations that hinder the distribution of 72 kg gas cylinders. The gas cylinder trolleys at RSUD Abepura are still manual. Therefore, this research offers an innovative solution, an electric trolley, as one of the methods to facilitate the distribution and traffic flow of oxygen cylinders at RSUD Abepura. The research results show that the electric trolley provides a suitable and convenient solution for operators and medical personnel in distributing oxygen cylinders without being hindered by the incline of the hospital road, thereby improving time efficiency and service effectiveness at RSUD Abepura.